THE POLITICAL IMAGERY IN THE MEDIA - Raharjo, Agus (Jurnal Dinamika Hukum, 2016)
Nowadays, the world is really hectic about the word that can be hypnotizing the society, it called “imagery”. Image is belief as everything and able to change the direction or person’s view on something that was never be anything. Something or someone that was nothing, suddenly can be more worth within media action. That is why called the craziness of media, as the way to construct something to be greater.....